Partisipasi Masyarakat Mewujudkan Zero Stunting Melalui Program Jago Ceting di Kelurahan Kapasmadya Baru - Putri Melinda Sari; Aisya Septia Cahyaning P.; Linang Rizkika Akbar Jalu P; Ach. Fais Mauludin; Oktarizka Reviandini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Stunting is one of the health problems faced in the world, especially in poor and developing countries, including Indonesia. The problem of stunting in Indonesia is still a chronic problem and a top priority. Various efforts to deal with stunting in Indonesia have been carried out, such as in the city of Surabaya which launched the Jago Ceting program as an effort to accelerate the reduction in stunting rates. Stunting cases in the city of Surabaya are often experienced by the people of North Surabaya, specifically in Kapasmadya Baru Village. In implementing the Jago Ceting program, the government does not only need to collaborate with related agencies/departments but also needs to invite and involve the role of the citizen. This research aims to determine citizen participation in realizing zero stunting through the Jago Ceting program in the Kapasmadya Baru sub-district. The method used in this research is descriptive research using a qualitative approach. The results of this research show that the participation of the Kapasmadya Baru Village citizen in implementing the jago ceting program can be assessed as high. Apart from that, in the program implementation process, citizen involvement in the Jago Ceting program is a key aspect to reduce the increase in stunting rates in Kapasmdya Baru Village. Through citizen involvement, stunting rates can be controlled intensively. So it is easier for the government to find solutions to the citizens' needs regarding the stunting problem.